Design of Warehouse Information System for KCM Division Using Javascript - Novel, Nurillah Jamil Achmawati; Fasha, Adinda (Universitas Trilogi, 2024)
Increasingly advanced technological developments force business people to be adaptive, especially when there is an increase in production. The KCM division, one of the PT XYZ business units operating in the media sector, experienced increased production. This causes the production equipment to be borrowed irregularly, and information on the warehouse of production equipment is also difficult to find. The Warehouse Information System is the solution to this problem. This research aims to create a warehousing information system that records all information on borrowing production equipment, fulfills warehousing information needs, and solves several existing warehousing problems. This research method is an experimental one-shot case study designed with the Framework for the Applications of System Thinking (FAST) and using simple, easily accessible, and free tools, namely Google Spreadsheet and Javascript coding. The results of this research are that the KCM division's warehousing information system that has been created has been tested to be 100% capable of meeting information needs for borrowing production equipment and resolving existing warehousing problems based on system tests that have been carried out. It is recommended that this system be further developed in future research to overcome minor errors in coding.